MODEL SELECT DAN ULTIMATE UNTUK KASUS MULTIPLE DECREME - Hasriati
Abstract: Usual treatments of multiple decrement theory are on a nonselect basis, with all rates of decrement depending only on attained age. This theses develops the theory on a select basis, carried out fully in the stochastic framework. The relationship between select periods in a multiple decrement model and those of associated single decrement models is investigated.